Learning Coding Through Scratch Edugames for Elementary School Children - Setyaningsih; Nur Fajrie; Fina Fakhriyah (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This study aims to examine the effectiveness of using Scratch Edugame in enhancing coding skills among elementary school students. The research employs a qualitative approach, utilizing direct observations and questionnaires to gather data on students' engagement and understanding during coding lessons. The findings reveal that students demonstrated a high level of engagement and enthusiasm, actively exploring various command blocks in Scratch and collaborating with peers. Furthermore, students were able to solve basic coding problems independently, showcasing their problem-solving skills. The study concludes that Scratch, as an interactive and game-based learning tool, not only helps in teaching basic coding concepts but also fosters creativity, critical thinking, and collaboration among students. The use of Scratch in coding education contributes to a positive learning environment, enhancing students' motivation and confidence in technology-related subjects. This research highlights the potential of Edugame platforms like Scratch in elementary education, suggesting further exploration of its long-term impact on student learning.